Excellence in project management : an Icelandic study - Eyjólfur Eyfells 1983- (2014)
This paper covers the research of excellence in project management leadership and looks into what qualities define the successful project manager in Iceland. The research question is as follows: “What qualities define the IPMA Level B certified Icelandic project managers?” Where IPMA stands for the International Project Management Association. Qualitative research methods based on grounded theory were used and the research scope was limited to interviewing five Icelandic project managers who have acquired an IPMA Level B certification in project management. The findings of this paper are that the main qualities that define the Level B certified Icelandic project managers are communication and organisational skills, as well as honesty. In that sense, the results are in line with the project management literature used in this thesis, which also states these qualities as being highly important for the successful project manager. It leads to the conclusion that excellent Icelandic project managers have similar qualities as those generally described in the literature review and that in order to dig deeper into the issue, longer interviews with a larger number of subjects would be needed to be undertaken.